Beyond maternal death: improving the quality of maternal care through national studies of 'near-miss' maternal morbidity - Marian Knight; Colleen Acosta; Peter Brocklehurst; Anna Cheshire; Kathryn Fitzpatrick; Lisa Hinton; Mervi Jokinen; Bryn Kemp; Jennifer J Kurinczuk; Gwyneth Lewis; Anthea Lindquist; Louise Locock; et al. (NIHR Journals Library, 2016)
Background: Studies of maternal mortality have been shown to result in important improvements to women's health. It is now recognised that in countries such as the UK, where maternal deaths are rare, the study of near-miss severe maternal morbidity provides additional information to aid disease prevention, treatment and service provision. Objectives: To (1) estimate the incidence of specific near-miss morbidities; (2) assess the contribution of existing risk factors to incidence; (3) describe different interventions and their impact on outcomes and costs; (4) identify any groups in which outcomes differ; (5) investigate factors associated with maternal death; (6) compare an external confidential enquiry or a local review approach for investigating quality of care for affected women; and (7) assess the longer-term impacts. Methods: Mixed quantitative and qualitative methods including primary national observational studies, database analyses, surveys and case studies overseen by a user advisory group. Setting: Maternity units in all four countries of the UK. Participants: Women with near-miss maternal morbidities, their partners and comparison women without severe morbidity. Main outcome measures: The incidence, risk factors, management and outcomes of uterine rupture, placenta accreta, haemolysis, elevated liver enzymes and low platelets (HELLP) syndrome, severe sepsis, amniotic fluid embolism and pregnancy at advanced maternal age (≥ 48 years at completion of pregnancy); factors associated with progression from severe morbidity to death; associations between severe maternal morbidity and ethnicity and socioeconomic status; lessons for care identified by local and external review; economic evaluation of interventions for management of postpartum haemorrhage (PPH); women's experiences of near-miss maternal morbidity; long-term outcomes; and models of maternity care commissioned through experience-led and standard approaches. Results: Women and their partners reported long-term impacts of near-miss maternal morbidities on their physical and mental health. Older maternal age and caesarean delivery are associated with severe maternal morbidity in both current and future pregnancies. Antibiotic prescription for pregnant or postpartum women with suspected infection does not necessarily prevent progression to severe sepsis, which may be rapidly progressive. Delay in delivery, of up to 48 hours, may be safely undertaken in women with HELLP syndrome in whom there is no fetal compromise. Uterine compression sutures are a cost-effective second-line therapy for PPH. Medical comorbidities are associated with a fivefold increase in the odds of maternal death from direct pregnancy complications. External reviews identified more specific clinical messages for care than local reviews. Experience-led commissioning may be used as a way to commission maternity services. Limitations: This programme used observational studies, some with limited sample size, and the possibility of uncontrolled confounding cannot be excluded. Conclusions: Implementation of the findings of this research could prevent both future severe pregnancy complications as well as improving the outcome of pregnancy for women. One of the clearest findings relates to the population of women with other medical and mental health problems in pregnancy and their risk of severe morbidity. Further research into models of pre-pregnancy, pregnancy and postnatal care is clearly needed. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.